Odorant-sensitive adenylate cyclase: rapid, potent activation and desensitization in primary olfactory neuronal cultures. - Ronnett, G V (1991)
Using primary olfactory neuronal cultures, we have demonstrated rapid, potent increases in cAMP levels and adenylate cyclase [AC; ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] activity in response to odorants. Isobutyl-methoxypyrazine is active at 1 nM. Odorant enhancement is dependent on Ca2+ concentration with maximal effects at 10-100 microM. Biphasic temporal and concentration-related effects occur with all odorants. All odorants examined elicit desensitization with AC responses abolished when odorants are reapplied immediately after removal. When reapplied 1 min after removal, odorants elicit an AC response greater than on first exposure, implying a cellular "memory" for odorants.